2019
DOI: 10.1002/mnfr.201900088
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Protein Diets with Fixed Carbohydrate Content Promote Hyperphagia and Sympathetically Mediated Increase in Energy Expenditure

Abstract: Scope: Dietary protein restriction elicits hyperphagia and increases energy expenditure; however, less is known of whether these responses are a consequence of increasing carbohydrate content. The effects of protein-diluted diets with fixed carbohydrate content on energy balance, hormones, and key markers of protein sensing and thermogenesis in tissues are determined. Methods and results: Obesity-prone rats (n = 13-16 per group) are randomized to diets containing fixed carbohydrate (52% calories) and varying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 47 publications
4
38
1
Order By: Relevance
“…Accumulating evidence indicates that moderate protein restriction in rodents (5–8% protein kcal) stimulates FGF21 secretion from the liver which acts on β-klotho receptors in the brain to promote hyperphagia ( 34 36 ) ( Figure 1 ). We have also shown that such hyperphagic responses to protein dilution are a consequence of increased meal size in rodents ( 31 ). The hyperphagic responses to moderate protein dilution are also associated with reduction in circulating concentrations of leptin and IGF-1, increased plasma ghrelin, and upregulation of orexigenic neuropeptide Y transcripts in the rodent hypothalamus ( 27 , 31 , 37 , 38 ).…”
Section: Regulation Of Food Intake By Low Protein Dietsmentioning
confidence: 83%
See 3 more Smart Citations
“…Accumulating evidence indicates that moderate protein restriction in rodents (5–8% protein kcal) stimulates FGF21 secretion from the liver which acts on β-klotho receptors in the brain to promote hyperphagia ( 34 36 ) ( Figure 1 ). We have also shown that such hyperphagic responses to protein dilution are a consequence of increased meal size in rodents ( 31 ). The hyperphagic responses to moderate protein dilution are also associated with reduction in circulating concentrations of leptin and IGF-1, increased plasma ghrelin, and upregulation of orexigenic neuropeptide Y transcripts in the rodent hypothalamus ( 27 , 31 , 37 , 38 ).…”
Section: Regulation Of Food Intake By Low Protein Dietsmentioning
confidence: 83%
“…Consistent with these studies that were mostly conducted in vitro and with amino acids, we ( 27 ) and others ( 28 30 ) showed that a similar pathway for sensing dietary protein deficiency also operates in the liver to upregulate hepatic FGF21 expression and secretion. Interestingly, we found that similar amino acid sensing pathways were also upregulated in the duodenum ( 31 ) suggesting that the intestine may detect protein deficiency prior to the liver, and/or that the intestinal sensing may serve to amplify the hepatic response to protein restriction. Independent of sensing by gut-associated tissues, amino acid deprivation causes a rapid anorexic response that is triggered by GCN2 signaling in the piriform cortex ( 32 , 33 ).…”
Section: Regulation Of Food Intake By Low Protein Dietsmentioning
confidence: 96%
See 2 more Smart Citations
“…Low protein intake was positively associated with metabolically healthy obesity in women [ 8 ]. In rats, mild (10% of total energy intake (TEI)) to moderate protein restriction (5% of TEI) is associated with hyperphagia and increases energy expenditure through activation of the sympathetic system [ 9 ]. Additionally, authors found similar lean mass in the group of rats with a 10% protein diet matched in protein intake to the 5% protein group, suggesting that the intake of dietary protein, but not calorie intake is necessary to preserve lean body mass.…”
Section: Using Proteins To Treat Obesitymentioning
confidence: 99%